2017
DOI: 10.1111/cmi.12803
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal dissemination to the central nervous system requires the vacuolar calcium transporter Pmc1

Abstract: Cryptococcus neoformans is a basidiomycetous yeast and the cause of cryptococcosis in immunocompromised individuals. The most severe form of the disease is meningoencephalitis, which is one of the leading causes of death in HIV/AIDS patients. In order to access the central nervous system, C. neoformans relies on the activity of certain virulence factors such as urease, which allows transmigration through the blood-brain barrier. In this study, we demonstrate that the calcium transporter Pmc1 enables C. neoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…As proven in other studies, the disruption of Ca 2+ homeostasis components is important for cryptococcal pathogenicity ( 29 33 , 51 ). To determine whether disruption of Ncs1-mediated calcium homeostasis also contributes to pathogenicity, we compared the virulence of the ncs1Δ mutant strain to that observed for the WT and ncs1Δ :: NCS1 strains in a mouse inhalation model of cryptococcosis.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…As proven in other studies, the disruption of Ca 2+ homeostasis components is important for cryptococcal pathogenicity ( 29 33 , 51 ). To determine whether disruption of Ncs1-mediated calcium homeostasis also contributes to pathogenicity, we compared the virulence of the ncs1Δ mutant strain to that observed for the WT and ncs1Δ :: NCS1 strains in a mouse inhalation model of cryptococcosis.…”
Section: Resultssupporting
confidence: 56%
“…Ncs1 activity is essential for C. neoformans virulence. As proven in other studies, the disruption of Ca 2ϩ homeostasis components is important for cryptococcal pathogenicity (29)(30)(31)(32)(33)51). To determine whether disruption of Ncs1-mediated calcium homeostasis also contributes to pathogenicity, we compared the virulence of the ncs1⌬ mutant strain to that observed for the WT and ncs1⌬::NCS1 strains in a mouse inhalation The transcript levels of genes encoding the calcium transporters, CCH1 and MID1, were evaluated using RT-qPCR.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, calcineurin regulates calcium homeostasis through the transcription factor Crz1 in yeast (Matheos et al 1997;Stathopoulos and Cyert 1997). In C. neoformans, calcineurin and Crz1 positively regulate expression of the VCX1 gene and the PMC1 gene encoding the vacuolar calcium transporter Pmc1 to confer higher tolerance to calcium (Kmetzsch et al 2010(Kmetzsch et al , 2013Chow et al 2017;Squizani et al 2017). Several studies have shown that the calcineurin/Crz1 regulatory network has been extensively rewired in different fungal species (Yoshimoto et al 2002;Kim et al 2010;Soriani et al 2010;Chatfield-Reed et al 2016;Chow et al 2017), which may account for the high calcium sensitivity observed in cna1D and cnb1D mutants in Cryptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…In fungi, two systems are responsible for sequestering cytoplasmic Ca 2+ ions into the vacuole, namely, the H + /Ca 2+ exchanger Vcx1p (911), which uses the proton gradient across the vacuolar membrane (generated by the V-ATPase) to drive Ca 2+ transport, and the P-type ATPase Pmc1p (11, 12). Both Pmc1p and Vcx1p are required for Cryptococcus neoformans to colonize lung or brain tissue in a mouse model of infection (1315). While Aspergillus fumigatus, a major cause of pulmonary as well as disseminated infections of humans, has three Pmc1p homologues ( PMCA , PMCB , and PMCC ), with PMCC seemingly essential for viability and PMCA required for virulence in a neutropenic mouse model of invasive pulmonary aspergillosis (16).…”
Section: Introductionmentioning
confidence: 99%